Function of PIN1 in Cancer Development and Its Inhibitors as Cancer Therapeutics - Yu, Ji Hoon; Im, Chun Young; Min, Sang-Hyun (Frontiers in Cell and Developmental Biology, 2020)
Peptidyl-prolyl isomerase (PIN1) specifically binds and isomerizes the phosphorylated serine/threonine–proline (pSer/Thr–Pro) motif, which results in the alteration of protein structure, function, and stability. The altered structure and function of these phosphorylated proteins regulated by PIN1 are closely related to cancer development. PIN1 is highly expressed in human cancers and promotes cancer as well as cancer stem cells by breaking the balance of oncogenes and tumor suppressors. In this review, we discuss the roles of PIN1 in cancer and PIN1-targeted small-molecule compounds.